La imputabilidad como presupuesto de la culpabilidad en los delitos cometidos por adolescentes infractores. - Manobanda, Raúl O. (2023)
The objective of this paper is to analyze imputability as an assumption of guilt in crimes committed by adolescent offenders, through doctrinal and jurisprudential foundations, so that those under 18 and over 16 years of age are fully attributable under the doctrinal precepts and the Comprehensive Organic Criminal Code, since, in Ecuador, there has been a high rate of crimes in which there is participation of adolescents protected by the theory of non-imputability, and that negatively affects the ability of organs of justice in combating impunity, which makes it necessary to address this serious social problem that threatens citizen security, within this research report the qualitative approach has been used, the level of descriptive, explanatory, relational and documentary research , and the method used in is analytical. We can conclude that adolescents can be considered attributable taking into account their degree of discernment as a human being and their evolutionary development, which gives them an aptitude that allows them to understand each of the acts they perform when they cause crimes with full use. of their intellectual faculties, with intent and freedom, that is to say with full will, for which they must be imputable and consequently be entitled to the corresponding penalty according to the crime committed.